Tackling Hypotheticals in Helminth Genomes - Palevich, Nikola (2018)
Advancements in genome sequencing have led to the rapid accumulation of uncharacterized ‘hypothetical proteins’ in the public databases. Here we provide a community perspective and some best-practice approaches for the accurate functional annotation of uncharacterized genomic sequences.